Alternativas al uso del permanganato de potasio como reductor de tono en el efecto localizado en la industria textil. (2023)
This document raises the possibility of replacing potassium permanganate in the textile industry as a localized tone reducer to create natural wear effects in garments whose textile base is denim. This project seeks to replace potassium permanganate from the textile industry in the laundry area, due to its high degree of contamination and the health risks that this product represents when in contact with it for a long time. Potassium permanganate is a substance widely used in industry, it has various applications as a disinfectant, oxidizing agent in water treatment, in the metallurgical and pharmaceutical industries, among others. However, information has been found on the different health problems that this substance generates in the long term when exposed for a considerable time, the health risks are associated with “Manganism”.